Pharmacogenomic landscape of TNF inhibitors in the Middle Eastern Qatari population - Jan, Zainab; Velayutham, Dinesh; Mifsud, Borbala; Jithesh, Puthen Veettil (Frontiers in Immunology, 2025)
IntroductionTumor necrosis factor alpha (TNF-α) is an important cytokine that frequently contributes to the pathogenicity of autoimmune diseases. Therefore, TNF inhibitors (TNFi) are used to treat autoimmune diseases. However, around 40% of the patients do not respond to TNFi, with genetic variants being a contributor to this variance. The prevalence of genetic variants affecting TNFi response in Middle Eastern populations is still not understood.MethodsWe assessed the distribution of variants in 111 genes associated with TNFi in 14,387 Qatari individuals using whole genome sequencing data.ResultsOf the 151 known pharmacogenomic variants associated with response to TNFi, approximately half have significantly different allele frequency distribution in the Qatari population compared to other world populations from the gnomAD dataset. High frequency of rs1800629 (TNF), rs1800896 (IL10), and rs1143634 (IL1B) variants are observed, which are known to be associated with responses to Etanercept and Infliximab. Moreover, we identified that PSORS1C1 has the highest CAPLoF (cumulative allele probability) scores for loss-of-function variants, which is associated with response to Etanercept and Adalimumab.DiscussionThe findings of this study will enhance our understanding of the pharmacogenomics of TNF inhibitors in Qatar and beyond, while also supporting the study of genetics in underrepresented populations.